Clinical and Laboratory Characterization of Hemodialysis Patients in Relation to Survival Outcomes at a Tertiary Referral Hospital in Indonesia - Sipayung, Elisabeth; Nariata, I Wayan; Yassir; Satyawati, Rumaisah; Wijaya, Surya Oto; Budi, Gesang Setia; Anitha; Rivaldiansyah; Maemun, Siti; Widiantari, Aninda Dinar (Universitas Airlangga, 2025)
Introduction: Despite advancements in hemodialysis care, disease progression and outcomes in adults with various comorbidities, particularly in Indonesia’s overburdened tertiary hospitals, remain poorly characterized, limiting tailored care strategies. This study analyzed clinical characteristics and laboratory parameters among hemodialysis patients at Sulianti Saroso Infectious Disease Hospital, Jakarta, Indonesia, with stratification by survival outcomes. Methods: We conducted a retrospective cohort study of adults (>18 years) undergoing hemodialysis at Sulianti Saroso Infectious Disease Hospital between March and July 2024. Using purposive sampling, we analyzed 27 cases with documented laboratory parameters (i.e., blood urea nitrogen (BUN), serum creatinine, and estimated glomerular filtration rate (eGFR)) and clinical outcomes. Associations between outcomes and laboratory/clinical variables were assessed using Fisher’s exact test and logistic regression (p<0.05). Results: Mortality was reported in 25.9% of patients, including one who passed away due to complications related to coronavirus disease 2019 (COVID-19) shortly after being discharged. The leading indication for hemodialysis was hyperuricemia (85.2%), followed by chronic kidney disease. Nearly half of the patients (48.1%) had comorbid diabetes mellitus. Diabetic nephropathy was a key contributor to elevated urea levels. Prevalent complications reported among the patients included sepsis (70.4%) and glomerular disease (40.7%). Conclusion: This study found an association between diabetes mellitus and mortality in chronic kidney disease patients who underwent hemodialysis. Severe uremia, marked by elevated BUN levels, and symptomatic complications such as shortness of breath were observed, indicative of advanced disease progression. Earlier detection and optimized management are necessary to mitigate preventable morbidity in high-risk populations. Highlights: 1. This study examined undercharacterized hemodialysis patients at an Indonesian tertiary hospital, focusing on high comorbidity burdens and outcomes. 2. Severe kidney disease and high mortality were observed, driven by comorbidities such as diabetes mellitus, hypertension, coronavirus disease 2019 (COVID-19), and infectious diseases (drug-resistant tuberculosis and hepatitis B/C). 3. The findings underscore the importance of optimized risk stratification and early intervention for end-stage renal failure in patients with both communicable and non-communicable disease comorbidities.